Evaluating the Codesigning Dementia Diagnosis and Post‐Diagnostic Care (COGNISANCE) project: Dementia care research (research projects; nonpharmacological)/Community care. (7th December 2020) - McAiney, Carrie A; Vedel, Isabelle; Doucet, Shelley; Luke, Alison; Jarrett, Pamela; Team, COGNISANCE
Abstract: Background: Persons with dementia and their family/friend care partners often report poor experiences at the time a dementia diagnosis was given and in the supports provided following the diagnosis. Such experiences often include a lack of information, a lack of support, and limited or no hope. While there are national guidelines that outline the steps required to make a dementia diagnosis, there is limited information about how best to engage persons with dementia and their care partners and communicate this information to them. There are also few resources to support individuals and care partners in navigating this challenging journey. The "Codesigning dementia diagnosis and post‐diagnostic care" (COGNISANCE) project aims to develop and evaluate toolkits and behaviour change campaigns for: 1) members of the at‐risk public and 2) health and social care providers to improve the dementia diagnosis experience and the supports provided following a diagnosis. The purpose of this poster is to describe the process of developing an evaluation plan, together with persons living with dementia and their care partners, that will be implemented in the five countries participating in COGNISANCE: Canada, Australia, Netherlands, United Kingdom, and Poland. Method: The evaluation plan is being informed by social marketing theories and guided by the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE‐AIM) framework. Working collaboratively with persons living with dementia and care partners, and a large international team, we are developing a comprehensive plan to evaluate the implementation and effectiveness of the behaviour change toolkits and campaigns. Result: We will describe the process used to develop the evaluation plan. This includes our experiences working together with persons living with dementia and their care partners, as well as our international collaborators, to develop a plan that achieves our objectives and is feasible to implement across the participating countries. Conclusion: Findings from the COGNISANCE evaluation will inform opportunities to spread the toolkits and campaigns within the participating countries, as well as the development of an implementation playbook, a resource aimed to support developing countries in creating and implementing their own toolkits and campaigns.